Investigating relationships between stakeholders' pressure, eco-control systems and hotel performance. (October 2016) - Abdel-Maksoud, Ahmed; Kamel, Hany; Elbanna, Said
Abstract: Stakeholders' pressure motivates the deployment of systems of environmental management control. Nevertheless, few insights are available regarding the impact of stakeholders' pressure on the extent to which eco-control systems are used. Findings from previous research on eco-control are said to be inconclusive, due to the lack of empirical evidence. In addition, the literature on hotels/tourism indicates a scarcity of studies investigating the factors associated with the use of these systems in the hotel sector. In this study, to help fill this gap, we contribute to the existing literature. We investigate, empirically, the associations between the impact of stakeholders' pressure and the use of eco-control systems, and whether the extent of using these systems is associated with hotel performance in the United Arab Emirates (UAE). Our findings conclude that the impact of stakeholders' pressure influences the extent of using eco-control systems in UAE hotels. However, contrary to expectations, the extent of using these systems is not significantly associated with hotel performance. Our findings and interpretations could reflect 'practice variation' in the adoption of eco-control systems in UAE hotels. It could be that UAE hotels do not capitalize on the implications the adoption of these systems could have on their performance. The academic and practical implications of our findings are discussed.